LEVEL OF PHYSICAL ACTIVITY AND SMOKING - Camapum Billerbeck, Nicole; Percilia Borges, Leydianne (International Journal of Movement Science and Rehabilitation, 2019)
Smoking is a worldwide public health problem that generates a great deal of government spending on treating diseases caused by it and can be considered the leading cause of preventable death worldwide. Several degenerative chronic diseases are related that associated with sedentary lifestyle cause several damages to smokers. In contrast, the practice of regular exercise can promote changes in healthy eating patterns, control in the use of cigarettes and alcohol. Thus, the objective of this study was to identify the profile of smokers as well as the relationship between the adoption of regular practice of physical activities and smoking cessation. This is a bibliographic review. Books, scientific articles and periodicals related to the theme were used. Through the researched studies it was possible to identify that in Brazil the proportion of men who smoke is higher in all age groups when compared to women. The age group with the highest prevalence of smokers is from 20 to 49 years and there is also a significant increase in tobacco use in younger age groups and physical activity can be a strong ally in tobacco control and, consequently, associated diseases.